Dampak Keberadaan Pasar Modern (Alfamidi) Terhadap Pendapatan Pedagang Tradisional Di Kabupaten Halmahera Utara - Philep Njonjie; Sahrul Hi. Posi (Universitas Pendidikan Ganesha, 2022)
The establishment of the Alfamidi Outlet in North Halmahera Regency is a threat to traditional market traders because the types of goods sold are relatively the same. Consumers can determine preferences between modern markets and traditional markets. The purpose of this study was to determine the impact before and after the arrival of the modern market (Alfamidi) on the income of traders in traditional markets. The scope of this research is the traditional market business in North Halmahera Regency by dividing the distribution of the sample distribution proportionally in several sub-districts whose traditional market locations are close to the modern market (Alfamidi). This study uses a qualitative method with interview media. The results of the study show that the number of traders' income which decreased after the presence of Alfamidi was 58 percent, experienced an increase in income of 11 percent, while there was no effect by 31 percent. Although the impact has not been so great, traditional market traders should make changes to their strategies and provide good facilities for consumers to be able to compete with modern markets. The government must also pay attention to traditional markets in an effort to improve the quality of goods sold and maintain price stability. Market traders must also be able to increase their business and be able to maintain cleanliness and comfort so that consumers do not switch to modern markets.